Indigenous Women's Voices 20 Years on from Linda Tuhiwai Smith's Decolonizing Methodologies - Lee, Emma; Evans, Jennifer (Bloomsbury Academic, 2021)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. When Linda Tuhiwai Smith's Decolonizing Methodologies was first published, it ignited a passion for research change that respected Indigenous peoples and knowledges, and campaigned to reclaim Indigenous ways of knowing and being. At a time when Indigenous voices were profoundly marginalised, the book advocated for an Indigenous viewpoint which represented a daily struggle to be heard, and to find its place in academia. Twenty years on, this collection celebrates the breadth and depth of how Indigenous writers are shaping the decolonizing research world today. With contributions from Indigenous female researchers, this collection offers the much needed academic space to distinguish methodological approaches, and overcome the novelty confines of being marginal voices.